Amodiaquine and Ciprofloxacin Combination in Plasmodiasis Therapy - Peace Mayen Edwin Ubulom; Chinweizu Ejikeme Udobi; Mark Iheukwumere Madu (Journal of Tropical Medicine)
Objective. The study was designed to determine the efficacy of combined Amodiaquine and Ciprofloxacin in plasmodiasis therapy. Method. The in vivo antiplasmodial effect of different dosage levels of Amodiaquine, Ciprofloxacin, and their combinations against Plasmodium berghei berghei was evaluated using Swiss albino mice. Results. Amodiaquine (a known antiplasmodial agent) had a fairly significant antiplasmodial effect reducing the parasites for every 100 red blood cells (RBC) from 66 to 16 (75.75%) at the tolerable dosage level of 7.5 mg/kg body weight while Ciprofloxacin (an antibiotic known to have antimalarial effect) showed an insignificant antiplasmodial effect reducing the parasites for every 100 RBC from 65 to 64 (1.53%) at the tolerable dosage level of 10.7 mg/kg body weight. Conversely, the combination therapy of Amodiaquine and Ciprofloxacin had a significant antiplasmodial effect at all the doses administered. The combination of 7.5 mg/kg of Amodiaquine and 12.8 mg/kg of Ciprofloxacin, however, showed the most significant antiplasmodial effect of the doses used reducing the number of parasites per 100 RBC from 60 to 10 (83.33%). Conclusions. Appropriate Amodiaquine and Ciprofloxacin combination will be effective for the treatment of malaria and better than either Amodiaquine or Ciprofloxacin singly at their recommended dosage levels.